1994
DOI: 10.2135/cropsci1994.0011183x003400010020x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Differences among Lycopersicon Species and Triticum aestivum Cultivars

Abstract: Leaf photosynthesis rate (A) and water use efficiency expressed as A/gs (gs, stomatal conductance) are controlled by stomatal properties and leaf internal anatomical and biochemical/physiological characteristics. Two germplasm entries were selected from each of the genera Triticum and Lycopersicon with contrasting drought resistance. Both drought resistant entries (L. pennellii and T. aestivum cv. TAM W‐ 101) had the greater A/gs within each pair. Of the two entries with high A/gs, L. pennellii had lower A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…In wheat, variation in photosynthetic water-use efficiency has been reported to result from differences in photosynthetic capacity or in stomatal conductance (Condon et al 1990;Morgan & LeCain 1991;Martin, Kebede & Rilling 1994). In the present experiment, variation in stomatal conductance rather than in the rate of photosynthesis caused the differences in photosynthetic water-use efficiency, as found previously for eight wheat genotypes by Morgan et al (1993) and for 10 common bean cultivars by Ehleringer (1990).…”
Section: Water-use Efficiencysupporting
confidence: 80%
“…In wheat, variation in photosynthetic water-use efficiency has been reported to result from differences in photosynthetic capacity or in stomatal conductance (Condon et al 1990;Morgan & LeCain 1991;Martin, Kebede & Rilling 1994). In the present experiment, variation in stomatal conductance rather than in the rate of photosynthesis caused the differences in photosynthetic water-use efficiency, as found previously for eight wheat genotypes by Morgan et al (1993) and for 10 common bean cultivars by Ehleringer (1990).…”
Section: Water-use Efficiencysupporting
confidence: 80%
“…This confirms the results of Zhang et al (1998) and Stegman et al (1980), who reported that water stress might increase TE. The variation in TE could be interpreted on the basis of photosynthetic capacity and stomatal conductance of the plants (Condon et al, 1990; Martin et al, 1994). Theoretically, more accessible water is conducted to more photosynthetic capacity, and thus, more gas is exchanged in the plants.…”
Section: Resultsmentioning
confidence: 99%
“…3b). A N / g s and δ 13 C values have been reported to be lower in tomato crop cultivars when compared to wild tomato species (Martin & Thorstenson 1988; Martin, Kebede & Rilling 1994; Martin, Tauer & Lin 1999; Comstock et al . 2005; Easlon & Richards 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3b). tomato species (Martin & Thorstenson 1988;Martin, Kebede & Rilling 1994;Martin, Tauer & Lin 1999;Comstock et al 2005;Easlon & Richards 2009). It is remarkable that AN/gs and d 13 C values for the TR accessions studied here were similar or even higher than those previously reported for wild tomato species.…”
Section: Variations In the Responses To Drought Of Gas-exchange Amongmentioning
confidence: 99%